Immunohistochemical analysis for acetylcholinesterase and choline acetyltransferase in mouse cerebral cortex after traumatic brain injury - HORIO, Tomoyo; OZAWA, Aisa; KAMIIE, Junichi; SAKAUE, Motoharu (Journal of Veterinary Medical Science, 2020)
The regulation of glial cells, especially astrocytes and microglia, is important to prevent the exacerbation of a brain injury because over-reactive glial cells promote neuronal death. Acetylcholine (ACh), a neurotransmitter synthesized and hydrolyzed by choline acetyltransferase (ChAT) and acetylcholinesterase (AChE), respectively, in the central nervous system, has the potential to regulate glial cells’ states, i.e., non-reactive and reactive states. However, the expression levels of these ACh-related enzymes in areas containing reactive glial cells are unclear. Herein we immunohistochemically investigated the distributions of AChE and ChAT with reactive glial cells in the cryo-injured brain of mice as a traumatic brain injury model. Immunohistochemistry revealed AChE- and ChAT-immunopositive signals in injured areas at 7 days post-injury. The signals were observed in and around glial fibrillary acidic protein (GFAP)- or CD68-immunopositive cells, and the numbers of cells doubly positive for GFAP/AChE, GFAP/ChAT, CD68/AChE, and CD68/ChAT were significantly increased in injured areas compared to sham-operated areas. Enzyme histochemistry for AChE showed intensely positive signals in injured areas. These results suggest that reactive astrocytes and microglia express and secrete AChE and ChAT in brain-injury areas. These glial cells may adjust the ACh concentration around themselves through the regulation of the expression of ACh-related enzymes in order to control their reactive states.